2021
DOI: 10.18203/2320-6012.ijrms20215037
|View full text |Cite
|
Sign up to set email alerts
|

A study on socio-clinical profile and associated risk factors of stroke patients admitted to neurology department of SCB medical college, Cuttack, Odisha

Abstract: Background: Non-communicable diseases (NCDs) are ragging reality of today’s world and have moved up the priority list of most countries worldwide including India. Objectives were to find out prevalence of different types of strokes among the patients admitted in neurology department of SCB medical college, to study socio-clinical profiles of admitted stroke patients and to find out associated risk factors with different types of strokes.Methods: Cross-sectional hospital-based study in neurology ward of SCB MCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The aim of the study was to find the prevalence of types of strokes among the patients admitted in the neurology department of SCB medical college, to assess demographic profiles of patients and to find out the associated risk factors of strokes. The risk factors were hypertension (63.3%), Diabetes mellitus 37%, and alcohol intake 53.9% [25] . In a systematic analysis of the Global Burden of Disease study on "Global, regional and national burden of stroke and its risk factors" showed that in 2019 12.2 million incidents of stroke, 101 million prevalent of stroke cases and 6.55 million death from stroke.…”
Section: Need Of the Studymentioning
confidence: 99%
“…The aim of the study was to find the prevalence of types of strokes among the patients admitted in the neurology department of SCB medical college, to assess demographic profiles of patients and to find out the associated risk factors of strokes. The risk factors were hypertension (63.3%), Diabetes mellitus 37%, and alcohol intake 53.9% [25] . In a systematic analysis of the Global Burden of Disease study on "Global, regional and national burden of stroke and its risk factors" showed that in 2019 12.2 million incidents of stroke, 101 million prevalent of stroke cases and 6.55 million death from stroke.…”
Section: Need Of the Studymentioning
confidence: 99%